Recent advances in transition-metal-free direct C–C and C–heteroatom bond forming reactions - Mehta, Vaibhav P.; Punji, Benudhar (RSC Advances, 2013)
The efficient generation of biaryl compounds and heterocycles via the advent of the transition-metal-free coupling reaction constitutes an important development in the last few years. Although early methods for the construction of such molecules involved transition metals, recent advances in the field have witnessed a myriad of elegant reports without the use of metal sources. The serendipitous discovery and observation of synthetic chemists have realized that there lies a great potential in exploiting the inherent reactivity of molecules in absence of transition metal. The key to the success of such coupling reactions is the use of a strong base, oxidant and a catalytic amount of N-donor ligands which contribute significantly. This review aims to highlight the recent progress in the field of transition-metal-free direct C–C and C–heteroatom bond forming reactions via the use of a strong base and (or) an oxidant.